UNIVERSITY EXTENSION IN PHYSICAL EDUCATION IF GOIANO: ACTIONS AND POSSIBILITIES (Fiep Bulletin - online, 2025)
This article addresses the importance of university extension in the Physical Education program at IF Goiano, highlighting how this practice connects academic knowledge to social demands. The curricularization of extension is presented as a strategy to integrate teaching, research, and extension, promoting the ethical, critical, and responsible formation of students. The text describes successful extension actions developed within the program, focused on areas such as health and education, and emphasizes their positive impact on the community. The challenges faced in implementing extension, such as resistance to change and the need for more consistent evaluations, are discussed. The study reinforces the relevance of extension for professional training, showing how initiatives applied in practice can benefit various groups, from children to the elderly. The article concludes that curricularizing extension is essential to enhance academic training and expand the social impact of Physical Education.
Keywords: university extension; physical education; curricularization